2017
DOI: 10.51745/najfnr.1.1.20-29
|View full text |Cite
|
Sign up to set email alerts
|

Overview on main nutrition-related diseases in three countries from North Africa

Abstract: The aim of this review article is to give a holistic overview on the magnitude of nutrition-related diseases in the North African region and to outline major factors associated with the prevalence of these complications. A literature analysis was performed on PubMed and Google Scholar for data relating to nutrition-related diseases published between January 2007 and March 2017. The employed keywords were; “Algeria AND Morocco AND Tunisia AND Nutrition-Related diseases”. We focused firstly on the nutrition-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…One of the regions in the world facing a high risk of overnutrition is North Africa. Studies show a rising trend in childhood overweight and obesity in North Africa, especially, in Egypt, with the prevalence higher than most countries in the Middle East and Sub-Saharan Africa ( 15 , 16 ). A study among school-going children in Sohag, Egypt found that 17% of the participants were overweight and 15% were obese ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the regions in the world facing a high risk of overnutrition is North Africa. Studies show a rising trend in childhood overweight and obesity in North Africa, especially, in Egypt, with the prevalence higher than most countries in the Middle East and Sub-Saharan Africa ( 15 , 16 ). A study among school-going children in Sohag, Egypt found that 17% of the participants were overweight and 15% were obese ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reports show a rising trend in childhood overweight and obesity in North Africa, especially, in Egypt, with the prevalence higher than in most countries in the Middle East and Sub-Saharan Africa [15,16]. A study among school-going children in Sohag, Egypt found approximately 17% of the participants were overweight and 15% were obese [3].…”
Section: Introductionmentioning
confidence: 99%